Effectiveness of sustained silent reading as a library program to enhance and increase reading comprehension - Villegas, Lutgarda N.; Cabbab, Johann Frederick A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2016)
Students in public elementary schools these days have shown that their reading comprehension level is lower that what is expected of their age. In this regard, reading programs have been implemented among public elementary schools and one example is the Sustained Silent Reading (SSR). This research sought to determine if Sustained Silent Reading is effective as a library program to enhance and increase reading comprehension of students. Third grade students were divided into experimental and control groups and determined difference pertaining to the three reading comprehension levels based on the Philippine Informal Reading Inventory (Phil-IRI); frustration, instructional and independent. T-test analysis was used as a statistical tool to determine if there was a significant difference between having gone through SSR in a library and having gone through SSR in the common setting which is the classroom. It was also used to determine if there was a significant difference with the scores of the students before and after the reading program. Results showed that there were no significant differences between having the SSR in the library or in the classroom.
Thesis (Bachelor of Library and Information Science)
Keywords: Silent reading; Reading comprehension; Library programs